POLA PENYAJIAN INFORMASI DAN KEPUTUSAN INVESTOR YANG IRASIONAL - Herla Kusumawardhani; Luciana Spica Almilia (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
This study aims to examine the difference between the participants' investment decisions that informed good news followed by bad news rather than participants who informed bad news followed by good news on the pattern of presentation of Step by step and length series information. Design of Experiments in this study is 1x1x2 which is pattern of presentationf Step by step (SBS), a series of information length, and direction of evidence information (good news followed by bad news and bad news followed by good news). The hypothesis in this study were tested with the Mann-Whitney U test. The results from this study indicate that there is no difference between participants investment decisions that were informed of good news followed by bad news than participants who informed good news followed by bad news in the presentation of SBS meanwhile in series pattern length information in the investment decision-making. This suggests that investment decisions taken by investors is as Irrational. Non-compliance results with the theory that in acu caused by four factors that affect the internal validity of such selection, maturation, history, and testing.Keywords: Step by step; Sbs; No order Effect; Investment Decision.